Pengaruh Pendidikan Kewirausahaan, Motivasi Berwirausaha, Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa Program Studi S1 Manajemen Fakultas Ekonomi dan Ilmu Sosial Universitas Islam Negeri Sultan Syarif Kasim Riau - Sehani Sehani; Oktyan Safiqul Khoiry (Al-Manar Journal of Economic and Social Studies, 2024)
This research was conducted at the S1 Management Study Program, Faculty of Economics and Social Sciences, Sultan Syarif Kasim Riau State Islamic University, Tampan District, Pekanbaru City. The purpose of this study was to determine whether entrepreneurship education (X1), entrepreneurial motivation (X2), family environment (X3) affect the interest in entrepreneurship (Y). The method used in this study uses quantitative methods. The population in this study are active students of S1 Management Study Program who have taken entrepreneurship courses totaling 543 students. The sampling technique is to use purposive random sampling, namely sampling with certain conditions. Determination of the number of respondents in this study using the Slovin formula so as to obtain the number of respondents as many as 84 students. data analysis techniques in this study using SPSS 25. The results of the study explain that partially entrepreneurship education (X1) has a positive and significant effect on entrepreneurial interest (Y), entrepreneurial motivation (X2) has a positive and very significant effect on entrepreneurial interest (Y), while the family environment (X3) has no effect on entrepreneurial interest (Y). Simultaneously entrepreneurship education (X1), entrepreneurial motivation (X2), family environment (X3) affects the entrepreneurial interest in Undergraduate Management Study Program Students, Faculty of Economics and Social Sciences, State Islamic University of Sultan Syarif Kasim Riau.